Further results on Z-cyclic triplewhist tournaments - Finizio, Norman J.; Merritt, Adele J. (Utilitas Mathematica, 1999)
In this study we introduce three constructions that enable us to obtain Z-cyclic triplewhist tournaments on v players when v is of the form 3qpn where q ∈ {7, 11}, n is a positive integer and p ≡ 1 (mod 4) is a prime less than 2000. The results presented here extend those of two earlier studies related to Z-cyclic whist tournaments for which the number of players was of the same form but with additional restrictions on p and q.